2001
DOI: 10.1118/1.1339885
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry of 192Ir wires for LDR interstitial brachytherapy following the AAPM TG-43 dosimetric formalism

Abstract: Implementation of the AAPM Task Group 43 dosimetric formalism for 192Ir wires used as interstitial sources in low dose-rate (LDR) brachytherapy applications is investigated. Geometry factors, dose-rate constant values, radial dose functions, and anisotropy functions, utilized in this formalism, were calculated for various lengths of all commercially available wire source designs by means of a well-established Monte Carlo simulation code and an improved modification of the Sievert integral method. Results are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…As L increases, the trend for to decrease was previously observed for elongated 192 Ir sources 47,48 and also for 103 Pd sources. 2 Karaiskos et al estimated values for 192 Ir wires with 1 ≤ L ≤ 8 cm, which varied by a factor of three.…”
Section: B Tg-43 Dosimetry Parameterssupporting
confidence: 65%
See 1 more Smart Citation
“…As L increases, the trend for to decrease was previously observed for elongated 192 Ir sources 47,48 and also for 103 Pd sources. 2 Karaiskos et al estimated values for 192 Ir wires with 1 ≤ L ≤ 8 cm, which varied by a factor of three.…”
Section: B Tg-43 Dosimetry Parameterssupporting
confidence: 65%
“…They also found that these values could be corrected by the value of the geometry function at the reference position, 49 i.e., /G(r 0 , θ 0 ), to obtain constancy within 3%. 47 Meigooni et al determined values for 103 Pd wires with 0.5 ≤ L ≤ 5 cm, 2 which also varied by a factor of three, but did not correct for G(r 0 , θ 0 ) as done by Karaiskos et al to account for TABLE IV. Evaluation of dose superposition errors for the CivaThin sources with the prescription point located at P(Y = 0.5, Z = 0).…”
Section: B Tg-43 Dosimetry Parametersmentioning
confidence: 99%
“…͑b͒ The dose rate constant ⌳ is obtained in a way similar to that used by Karaiskos et al 7 by interpolating or extrapolating over the ⌳ values for 0.5 and 1 cm wires and correcting for the geometry dividing by G L ͑r = 1 cm, =90°͒ for both lengths:…”
Section: Iic the Two Lengths Based Linear Source Segmented Methods "mentioning
confidence: 99%
“…This source model has been widely studied in the literature using analytically derived Sievert 2 algorithms, experimental methods and Monte Carlo ͑MC͒ calculations. [3][4][5][6][7][8][9] Presently, the commercially available treatment planning systems approximate the dose rate distribution of the wires or elongated sources applying the superposition principle using one of the following methods:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation